2011
DOI: 10.1007/s00705-010-0894-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel TLR3 inhibitor encoded by African swine fever virus (ASFV)

Abstract: African swine fever virus (ASFV) encodes proteins that manipulate important host antiviral mechanisms. Bioinformatic analysis of the ASFV genome revealed ORF I329L, a gene without any previous functional characterization as a possible inhibitor of TLR signaling. We demonstrate that ORF I329L encodes a highly glycosylated protein expressed in the cell membrane and on its surface. I329L also inhibited dsRNA-stimulated activation of NFκB and IRF3, two key players in innate immunity. Consistent with this, expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 31 publications
2
68
0
3
Order By: Relevance
“…In addition to activation of NF‐κB signaling in LPS‐treated cells, LPS also activates JAK/signal transducer and activator of transcription (STAT) signaling pathway [46, 47], and JAK/STAT signaling is important on chemokine expression [48, 49]. To investigate the relationship of JAK‐STAT signaling pathway on LPS‐induced chemokine expression, BV2 cells were pre‐treated with JAK/STAT inhibitor, AG490, for 30 min, and then stimulated with 1 μg/mL LPS for 12 hr.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to activation of NF‐κB signaling in LPS‐treated cells, LPS also activates JAK/signal transducer and activator of transcription (STAT) signaling pathway [46, 47], and JAK/STAT signaling is important on chemokine expression [48, 49]. To investigate the relationship of JAK‐STAT signaling pathway on LPS‐induced chemokine expression, BV2 cells were pre‐treated with JAK/STAT inhibitor, AG490, for 30 min, and then stimulated with 1 μg/mL LPS for 12 hr.…”
Section: Resultsmentioning
confidence: 99%
“…Three immune evasion genes (G protein-coupled receptor (GPCR), tumor necrosis factor receptor (TNFR), and Bcl-2 genes) from another iridovirus have been detected, and the results showed that the genes could regulate apoptosis in fish cells (Huang 2007). And what's more, recent research also revealed that many large double-stranded DNA viruses could encode an array of host evasion molecules that interfere with signaling cascades and anti-viral responses (Mohamed and McFadden 2009;FaganGarcia and Barry 2011;de Oliveira et al 2011). It is likely that RGV also contains immune evasion genes in its genome, which may facilitate virus invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This latter effect seems specific to transcription factors that act through the N-terminal but not C-terminal domain of p300 (Granja et al, 2009). An ASFV Toll like receptor (TLR)3 inhibitor, encoded by the ASFV gene I329L has been identified (de Oliveira et al, 2011) which could reduce transcription of genes through its effect on the pattern recognition receptors (PPRs) and resultant downstream signalling pathways. In addition deletion of 6 members of multigene family 360 (MGF360) and 2 of multigene family 530 (MGF530), from a virulent isolate Pr4, was shown to result in an increased type I IFN response and induction of IFN stimulated genes (ISGs).…”
Section: Introductionmentioning
confidence: 99%